Attitudes towards protection of biodiversity in forests - Hedwall, Per-Ola (2004)
The focus of nature protection through area protection in Swedish forests has for a long time been on boreal, subalpine and alpine areas. Large areas have of this reason been protected in northern Sweden, while the protection of forest in southern Sweden, and especially in the temperate zone, have been almost neglected. Only 2,5 per cent of the land area in the southernmost county in Sweden, the county of Skåne, has some kind of protection today and considerably less of the forest is protected. Some possible reasons for this distorted balance of share of protected forest between northern and southern Sweden are: * The large share of state-owned forest in northern Sweden has facilitated the work with area protection. * The large share of forest owned by non-industrial private forest owners in southern Sweden and the relatively small estates in southern Sweden has been a hindrance in the implementation of area protections. * The long history of land use in southern Sweden has made it difficult to find areas with high nature values for protection, and these areas are very often scattered in the landscape. The need of protection of biodiversity in the forests of southern Sweden is largely due to the long history of land use. Southern Sweden has much more threatened species than northern Sweden, not only due to the land use history, but also due to the generally higher number of species in the south. The area of protected forest has however increased much in Skåne during recent years and many private forest owners have been involved in this process. The County Forestry Board of Södra Götaland has been the most active authority in the number of concerned estates and thereby influenced forest owners. The County Board of Skåne and the Swedish Environmental Protection Agency have implemented some new nature reserves and national parks. These areas are usually of larger size but concern in relation to their size fewer estates and thereby there are less forest owners influenced. The encroachment of these forms of ...